Learn more about

Refine search

Results (displaying matches 1-50 of 20561) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
3319.a.3319.1 3319.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^4 + x^3\) $\mathrm{USp}(4)$ 2
3391.b.3391.1 3391.b \(y^2 + (x^3 + x + 1)y = -x^5 - x^4\) $\mathrm{USp}(4)$ 2
3469.a.3469.1 3469.a \(y^2 + (x^3 + x + 1)y = x^5 - x^4 - 2x^3\) $\mathrm{USp}(4)$ 2
3571.a.3571.1 3571.a \(y^2 + (x^3 + x + 1)y = -2x^4 + x^2 - x\) $\mathrm{USp}(4)$ 2
3721.a.3721.1 3721.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 + 3x^2 + x\) $E_6$ 2
3969.b.35721.1 3969.b \(y^2 + (x^3 + x + 1)y = -2x^5 + 3x^4 - 3x^2\) $E_6$ 2
4021.a.4021.1 4021.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^2 + x\) $\mathrm{USp}(4)$ 2
4489.a.4489.1 4489.a \(y^2 + (x^3 + x + 1)y = x^5 - x\) $G_{3,3}$ 2
4673.a.4673.1 4673.a \(y^2 + x^3y = x^3 - x^2 - x + 1\) $\mathrm{USp}(4)$ 2
4925.b.4925.1 4925.b \(y^2 + x^3y = -x^4 - x^3 + x + 1\) $\mathrm{USp}(4)$ 2
4989.a.14967.1 4989.a \(y^2 + (x^3 + x + 1)y = x^5 - 2x^3 + x\) $\mathrm{USp}(4)$ 2
5026.a.35182.1 5026.a \(y^2 + (x^3 + 1)y = 4x^5 + 22x^4 + 46x^3 + 28x^2 + 5x\) $\mathrm{USp}(4)$ 2
5113.a.5113.1 5113.a \(y^2 + (x^2 + x + 1)y = x^6 - 2x^4 - x\) $\mathrm{USp}(4)$ 2
5170.b.10340.1 5170.b \(y^2 + (x^3 + x^2 + x)y = -2x^2 - x + 1\) $\mathrm{USp}(4)$ 2
5209.a.5209.1 5209.a \(y^2 + (x^3 + x + 1)y = x^4 + x^3 - x^2 - x\) $\mathrm{USp}(4)$ 2
5295.a.79425.1 5295.a \(y^2 + (x^3 + x^2 + 1)y = -x^3 + 3x + 2\) $\mathrm{USp}(4)$ 2
5329.b.5329.1 5329.b \(y^2 + (x^3 + x^2 + 1)y = x^3 - x\) $G_{3,3}$ 2
5331.a.15993.1 5331.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 + x^2 - x\) $\mathrm{USp}(4)$ 2
5414.a.10828.1 5414.a \(y^2 + (x^3 + 1)y = 2x^2 + x\) $\mathrm{USp}(4)$ 2
5449.b.5449.1 5449.b \(y^2 + (x^3 + x + 1)y = x^4 + 2x^3 + x^2\) $\mathrm{USp}(4)$ 2
5476.b.21904.1 5476.b \(y^2 + y = x^6 - x^2\) $G_{3,3}$ 2
5501.a.5501.1 5501.a \(y^2 + (x^3 + x^2 + 1)y = -2x^3 - 3x^2 + x + 2\) $\mathrm{USp}(4)$ 2
5547.b.16641.1 5547.b \(y^2 + y = x^6 - 3x^5 + x^4 + 3x^3 - x^2 - x\) $G_{3,3}$ 2
5599.a.5599.1 5599.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^2 - 2x\) $\mathrm{USp}(4)$ 2
5618.a.11236.1 5618.a \(y^2 + (x^3 + 1)y = -x^5 + x^4 + x^2 - x\) $G_{3,3}$ 2
5641.a.5641.1 5641.a \(y^2 + y = x^6 - x^5 - x^4 + 2x^3 - x\) $\mathrm{USp}(4)$ 2
5705.a.5705.1 5705.a \(y^2 + (x^3 + 1)y = x^5 + x^4 + x^3 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 2
5769.b.17307.1 5769.b \(y^2 + (x^3 + x + 1)y = x^5 - 3x^3\) $\mathrm{USp}(4)$ 2
5819.a.5819.1 5819.a \(y^2 + x^3y = x^4 - x^3 + 2x^2 - x + 1\) $\mathrm{USp}(4)$ 2
5911.b.5911.1 5911.b \(y^2 + (x^3 + x + 1)y = -2x^4 + x^3 - x^2\) $\mathrm{USp}(4)$ 2
6081.b.164187.1 6081.b \(y^2 + (x^3 + x^2 + 1)y = -2x^4 - 5x^3 + 5x + 2\) $\mathrm{USp}(4)$ 2
6201.a.241839.1 6201.a \(y^2 + (x^3 + 1)y = 2x^5 - 13x^3 + 21x^2 - 12x + 2\) $\mathrm{USp}(4)$ 2
6229.a.6229.1 6229.a \(y^2 + (x^3 + x + 1)y = -2x^4 + 3x^3 - 3x^2\) $\mathrm{USp}(4)$ 2
6291.e.56619.1 6291.e \(y^2 + (x^3 + x + 1)y = 2x^4 - x^2 - x\) $\mathrm{USp}(4)$ 2
6400.f.64000.1 6400.f \(y^2 + x^3y = -2x^4 - 3x^3 + x^2 + 6x + 4\) $E_4$ 2
6437.a.6437.1 6437.a \(y^2 + (x^3 + x^2 + x + 1)y = x^3 - 2x\) $\mathrm{USp}(4)$ 2
6443.a.6443.1 6443.a \(y^2 + y = x^5 - x^4 - 2x^3 + x^2 + x\) $\mathrm{USp}(4)$ 2
6463.a.6463.1 6463.a \(y^2 + (x^2 + x + 1)y = x^6 - x^4\) $\mathrm{USp}(4)$ 2
6511.a.6511.1 6511.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^4 - 2x^2 - x\) $\mathrm{USp}(4)$ 2
6718.a.13436.1 6718.a \(y^2 + (x^2 + x + 1)y = x^6 + x^5 - x^2 - x\) $\mathrm{USp}(4)$ 2
6845.a.6845.1 6845.a \(y^2 + x^3y = x^5 - 7x^3 - 16x^2 - 15x - 5\) $G_{3,3}$ 2
6869.a.6869.1 6869.a \(y^2 + (x^2 + x + 1)y = x^6 - x^4 - x^2 - x\) $\mathrm{USp}(4)$ 2
6982.a.13964.1 6982.a \(y^2 + (x^3 + 1)y = x^5 - 3x^3 + 2x\) $\mathrm{USp}(4)$ 2
7004.a.28016.1 7004.a \(y^2 + y = x^6 - 4x^4 - 4x^3 + x\) $\mathrm{USp}(4)$ 2
7165.a.7165.1 7165.a \(y^2 + (x^3 + 1)y = x^4 + x^3 - 2x^2\) $\mathrm{USp}(4)$ 2
7211.a.7211.1 7211.a \(y^2 + (x^3 + 1)y = -x^4 + 2x^3 - 2x^2\) $\mathrm{USp}(4)$ 2
7225.a.36125.1 7225.a \(y^2 + (x^3 + 1)y = -x^5 + 2x^4 - 3x^2 - x\) $G_{3,3}$ 2
7389.a.22167.1 7389.a \(y^2 + (x^3 + x^2 + x)y = -2x^4 + x^2 - 2x + 1\) $\mathrm{USp}(4)$ 2
7396.a.29584.1 7396.a \(y^2 + y = x^6 - 2x^4 + x^2\) $G_{3,3}$ 2
7403.a.7403.1 7403.a \(y^2 + y = x^5 + x^4 - 2x^3 - x^2 + x\) $\mathrm{USp}(4)$ 2
Next

Download all search results for